Preaching and Living Out the Gospel: A Confessional Reformed Theology of Mission - Yuzo Adhinarta (Veritas: Jurnal Teologi dan Pelayanan)
This article aims to respond to Gustav Warneck and MacGavran's critique of the deficit of missionary conscience in Protestantism, while building on Robert Recker, Fred Klooster, and Anthony Hoekema's findings that missionary conscience is not absent in Reformed confessions of faith. In particular, this article examines whether Reformed confessional documents provide guidelines in the theology and practice of mission for Reformed churches that can be used to develop a mission paradigm in the contemporary era. A thorough reading and critical exploration of the confessional documents and a reconstruction of the theology of mission in them show that they contain basic guidelines in the theology and practice of mission, especially in terms of the scope, motive, and expression of mission.